Rituximab plus high-dose chemotherapy (MegaCHOEP) or conventional chemotherapy (CHOEP-14) in young, high-risk patients with aggressive B-cell lymphoma: 10-year follow-up of a randomised, open-label, phase 3 trial. Issue 4 (April 2021) - Frontzek, Fabian; Ziepert, Marita; Nickelsen, Maike; Altmann, Bettina; Glass, Bertram; Haenel, Mathias; Truemper, Lorenz; Held, Gerhard; Bentz, Martin; Borchmann, Peter; Dreyling, Martin; Viardot, Andreas; et al.
Summary: Background: R-MegaCHOEP was the first phase 3 study comparing high-dose chemotherapy plus rituximab followed by autologous haematopoietic stem-cell transplantation (HSCT) with conventional chemotherapy plus rituximab in first-line therapy for patients aged 60 years or younger with high-risk aggressive B-cell lymphoma. Little is known about the long-term outcomes of these patients. We aimed to evaluate the long-term efficacy and safety of conventional chemotherapy versus high-dose chemotherapy after 10 years of follow-up in the R-MegaCHOEP trial. Methods: In this open-label, randomised, phase 3 trial done across 61 centres in Germany, patients aged 18–60 years with newly diagnosed, high-risk (age-adjusted International Prognostic Index [IPI] 2 or 3) aggressive B-cell lymphoma were randomly assigned (1:1, using Pocock minimisation) to eight cycles of conventional chemotherapy (cyclosphosphamide, doxorubicin, vincristine, etoposide, and prednisolone) plus rituximab (R-CHOEP-14) or four cycles of high-dose chemotherapy plus rituximab followed by autologous HSCT (R-MegaCHOEP). The trial was unmasked. Patients were stratified by age-adjusted IPI factors, presence of bulky disease (tumour mass ≥7·5 cm diameter), and treatment centre. The primary endpoint was event-free survival, analysed here 10 years after randomisation. 10-year overall survival, progression-free survival, conditional survival, relapse patterns, secondary malignancies, and molecular characteristics were also analysed. All analyses were done on the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT00129090 . Findings: Between March 3, 2003, and April 7, 2009, 275 patients were randomly assigned to R-CHOEP-14 (n=136) or R-MegaCHOEP (n=139). 130 patients in the R-CHOEP-14 group and 132 patients in the R-MegaCHOEP group were included in the intention-to-treat population. After a median follow-up of 9·3 years (IQR 5·1–11·1), 10-year event-free survival was 51% (95% CI 42–61) in the R-MegaCHOEP group and 57% (47–67) in the R-CHOEP-14 group (adjusted hazard ratio [HR] 1·3 [95% CI 0·9–1·8], p=0·23). 10-year progression-free survival was 59% (50–68) in the R-MegaCHOEP group and 60% (51–70) in the R-CHOEP-14 group (adjusted HR 1·1 [0·7–1·7], p=0·64). 10-year overall survival was 66% (57–76) in the R-MegaCHOEP group and 72% (63–81) in the R-CHOEP-14 group (adjusted HR 1·3 [0·8–2·1], p=0·26). Relapse occurred in 30 (16% [95% CI 11–22]) of 190 patients who had complete remission or unconfirmed complete remission; 17 (17%) of 100 patients in the R-CHOEP-14 group and 13 (14%) of 90 patients in the R-MegaCHOEP group. Seven (23%) of 30 patients had low-grade histology at relapse and had better outcomes compared with patients who relapsed with aggressive histologies. Lymphoma affected the CNS in 18 (28%) of 64 patients with treatment failure. 22 secondary malignancies were reported in the intention-to-treat population; in 12 (9%) of 127 patients in the R-CHOEP-14 group and ten (8%) of 126 patients in the R-MegaCHOEP group. Interpretation: Event-free survival and overall survival were similar between groups after 10 years of follow-up; outcomes were not improved in the R-MegaCHOEP group by high-dose chemotherapy and autologous HSCT. Patients who relapsed with aggressive histology showed a high incidence of CNS involvement and poor prognosis. For these patients, novel therapies are greatly warranted. Funding: Deutsche Krebshilfe (German Cancer Aid).